2022
DOI: 10.1016/j.joca.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary running attenuates behavioural signs of low back pain: dimorphic regulation of intervertebral disc inflammation in male and female SPARC-null mice

Abstract: Objective: To examine the effect of running exercise on behavioral measures of pain and intervertebral disc (IVD) inflammation in the SPARC-null mouse model. Methods: Male and female 8-month old SPARC-null and age-matched control mice received a home cage running wheel or a control, fixed wheel for 6 months. Behavioral assays were performed to assess axial discomfort (grip test) and radiating leg pain (von Frey, acetone tests) and voluntary running was confirmed. Expression of inflammatory mediators (TNF-a, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Co-culture models of degenerated IVDs and macrophages also suggest that IVD-produced IL-1β polarizes macrophages to a pro-inflammatory phenotype [ 78 ]. Recent studies also suggest that exercise limits pain and macrophage-mediated inflammation within the disc in mouse models [ 79 ]. Broad clearance of all macrophage subsets in vivo via clodronate liposomes limits production of inflammatory cytokines when Cd11b + cells from the disc are cultured in vitro [ 80 ], but an examination of the effects of macrophage clearance on disc degeneration was not described.…”
Section: Roles Of Macrophages In Disc Degenerationmentioning
confidence: 99%
“…Co-culture models of degenerated IVDs and macrophages also suggest that IVD-produced IL-1β polarizes macrophages to a pro-inflammatory phenotype [ 78 ]. Recent studies also suggest that exercise limits pain and macrophage-mediated inflammation within the disc in mouse models [ 79 ]. Broad clearance of all macrophage subsets in vivo via clodronate liposomes limits production of inflammatory cytokines when Cd11b + cells from the disc are cultured in vitro [ 80 ], but an examination of the effects of macrophage clearance on disc degeneration was not described.…”
Section: Roles Of Macrophages In Disc Degenerationmentioning
confidence: 99%
“…Enhanced production of proinflammatory molecules is observed during the pathogenesis of IVDD ( Lee et al, 2021 ). Various proinflammatory cytokines and chemokines have been reported to be associated with IVDD ( De Luca et al, 2020 ; Jacobsen et al, 2020 ), among which TNF-α has been considered a predominant factor and shown to play a detrimental role in IVDD development ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of SPARC decreased with aging and intervertebral disc degeneration. Moreover, it has been demonstrated that SPARC deletion accelerates IDD in mice (98,99). Histological analysis revealed that herniations of lower lumbar discs in SPARC-null mice occur as early as 14-month-old.…”
Section: Spontaneous Model 231 Genetically Modified Mice Modelmentioning
confidence: 99%
“…Certain gene deficiency impairs intervertebral disc metabolic homeostasis and structural integrity. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular protein involved in the pathogenesis of IDD (98). The expression level of SPARC decreased with aging and intervertebral disc degeneration.…”
Section: Spontaneous Model 231 Genetically Modified Mice Modelmentioning
confidence: 99%